(untitled) (Educação e Pesquisa, 2005)
The present article works in the perspective of Michel Foucault's governmentality, and makes use of his concept of govern with the purpose of discussing the authorities summoned and authorized in part of the discourse of the Brazilian educational media on school education circulated between 1999 and 2001. The discourse investigated is signified as integrating a set of govern mechanisms associated to the conduct of individuals in contemporary society. The analysis focuses on the strategies and techniques used in this discourse to instruct teachers on how to self-regulate and act for the good of education and of the development of Brazil. It demonstrates that school education is apprehended in the discourse investigated as a social problem, and translated as an object susceptible to intervention and regulation. Such intervention must be made by all, but some experts are called upon to teach us how we should behave and how to intervene in education. The argument developed here is that the educative media - through various technological operations, the use of specialists, and the production of new authorities in education - presents itself as an authority in education, putting to work heterogeneous mechanisms to instruct teachers on procedures they should apply to themselves so as to govern their our conduct, and to help in the govern process of others.